Culture Shock Relawan Asing di Kabupaten Karawang, Jawa Barat - Satria Ali Syamsuri; Fajar Hariyanto; Fardiah Oktariani Lubis (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2020)
Culture shock is pyschology name to describe the circumstance and feeling of someone facing different socio-culture environmental condition. This research examines the phenomenon of culture shock in the foreign volunteers in Karawang Regency, they are incorporated in an official government agency from United States namely Peace Corps. The foreign volunteers who become research informants in Indonesia are in teaching program for two years in school, in Batu Jaya and Cilamaya, Karawang Regency. This research using descriptive qualitative method to observe social phenomenon which produces descriptive data on the phenomenon that occurs in the foreign volunteers related to culture shock they experienced. The result of this research shows that the foreign volunteers experiencing level of culture shock on their new cultural environment in Indonesia, where the optimistic phase, the cultural problem phase, and the recovery phase are experienced by them. Until now, the foreign volunteers have entered the adjustment phase. Culture shock atau dalam bahasa Indonesia disebut dengan gegar budaya merupakan istilah psikologis untuk menggambarkan keadaan dan perasaan seseorang menghadapi kondisi lingkungan sosial budaya yang berbeda. Penelitian ini mengkaji fenomena culture shock pada relawan asing yang berada di Kabupaten Karawang, para relawan asing dalam penelitian ini tergabung dalam suatu lembaga resmi pemerintah yang berasal dari negara Amerika yaitu Peace Corps. Para relawan asing yang menjadi informan penelitian berada di Indonesia dalam program mengajar selama dua tahun di sekolah yang berada di Batu Jaya dan Cilamaya, Kabupaten Karawang.Penelitian ini menggunakan metode penelitian dekriptif kualitatif untuk mengamati fenomena sosial yang menghasilkan data deksriptif atas fenomena yang terjadi pada para relawan asing terkait gegar budaya atau culture shock yang dialaminya. Hasil penelitian ini menunjukkan bahwa para relawan asing mengalami tingkatan culture shock pada lingkungan budaya barunya di Indonesia, dimana fase optimistik, fase masalah kultural dan fase recovery dialami oleh para relawan asing, hingga pada saat ini para relawan asing memasuki fase penyesuaian.